Gramsci on Tahrir : Revolution and Counter-Revolution in Egypt - Smet, Brecht De (Reading Gramsci., 2016)
Explores the relevance of the Gramscian concept of passive revolution and Caesarism in the context of the Egyptian revolution and counter-revolution.